Robert King conducts a recreation of King George II's coronation ceremony with the King's Consort - Child, William 1606?-1697; Handel, George Frideric 1685-1759; Purcell, Henry 1659-1695; Handel, George Frideric 1685-1759; Tallis, Thomas approximately 1505-1585; Farmer, John active 1591-1601; Handel, George Frideric 1685-1759; Blow, John -1708; Handel, George Frideric 1685-1759; Gibbons, Orlando 1583-1625; Blow, John -1708; Handel, George Frideric 1685-1759 (A co-production Wahoo Production & Château de Versailles Spectacles, 2018)
In a splendid concert in Versailles' Royal Chapel, Robert King and the King's Consort take us on a musical journey back to 1727 for the coronation of George II of England! The musicians present a recreation of the event's original musical program, with highlights including all four of Handel's most celebrated coronation anthems--some of the most beautiful ceremonial works ever written for an English coronation! George II's 1727 coronation at Westminster Abbey was a truly magnificent event, full of sumptuous pomp set off by music of equal splendor and elegance. The young king-to-be charged Handel, the celebrated opera composer and recently naturalized British citizen, to write the music for the grand ceremony. His artistic efforts produced an impressive result: four coronation anthems for the enthronement ("Let thy hand be strengthened"), the unction ("Zadok the Priest"), the consecration ("The King shall rejoice") and the Queen's coronation ("My heart is Inditing"). The ceremony also intermingled fanfares and processions of drums and trumpets with an anthem by Child, plainchant settings by Blow, an antiphon by Purcell, a Te Deum by Gibbons, and Litanies by Tallis. Reconstruction of King George II's 1727 coronation ceremony in Westminster Abbey, designed and premiered by Robert King. Photo: © Conrad Allain
Keywords: Orchestral music; Fanfares; Coronation music; Choruses, Sacred (Mixed voices) with orchestra; Anthems; Concert films; Internet videos